2017
DOI: 10.1080/1343943x.2017.1304809
|View full text |Cite
|
Sign up to set email alerts
|

New winter oilseed rape varieties – seed quality and morphological traits depending on sowing date and rate

Abstract: Many studies have focused on research about impact of time and density of sowing on the agronomic characteristics of different crops. However, the number of studies investigating such a response on the qualitative composition of different types of winter oilseed rape varieties is still limited. The aim of the research was to determine the effect of sowing date and density on yield, protein and oil content and quality of winter oilseed rape varieties: open-pollinated, a typical hybrid of traditional type of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The results of our own research indicate that a significantly lower amount of rainfall in April, compared with the average of many years in the last year of the study, could have affected the increase in glucosinolate content. Many authors came to similar conclusions [13,[30][31][32][33][34], and stated that drought during flowering may affect the concentration of glucosinolate in rapeseed.…”
Section: The Content Of Glucosinolates Depending On the Climatic Condmentioning
confidence: 59%
See 3 more Smart Citations
“…The results of our own research indicate that a significantly lower amount of rainfall in April, compared with the average of many years in the last year of the study, could have affected the increase in glucosinolate content. Many authors came to similar conclusions [13,[30][31][32][33][34], and stated that drought during flowering may affect the concentration of glucosinolate in rapeseed.…”
Section: The Content Of Glucosinolates Depending On the Climatic Condmentioning
confidence: 59%
“…Similarly, Sikorska et al, [14] noted the lowest concentration of glucosinolates in the Monolit population form-on average 8.84 µM·g −1 , while the highest-on average 9.84 µM·g −1 was found in seeds of a restored hybrid form with a semi-dwarf growth type (PR 44D06). In turn, Rajtczak et al [13] showed that the seeds of the semi-dwarf hybrid PR45D03 were characterized by a much lower content of glucosinolates compared to the hybrid with traditional growth type (PR46W31) and the population cultivar (Californium).…”
Section: The Content Of Glucosinolates Depending On the Studied Cultimentioning
confidence: 99%
See 2 more Smart Citations
“…Authors include 6 different oilseed rape genotypes (Ahmadi, Okapi, Opera, L72, Karaj1 and SW102) and found that the seed yield at 60 and 80 plants m -2 in all varieties was significantly reduced compared to the 40 plants m -2 . In the study of different plant population (30, 40, 50 and 60 seeds m -2 ) by Ratajczak et al (2017) indicate that the lowest seed yield was obtained at 30 m -2 seeds (38.9 dt ha -1 ), while there was no statistically justified differences between yield of seeds of other sowing density and the yield ranged from 41.0 dt ha -1 (40 seeds m -2 ) to 41.4 dt ha -1 (60 seeds m -2 ). Zhang et al (2012) also found yield decrement with increasing plant population and they statted that the highest seed yield per plant was at 36 plants m -2 .…”
Section: Discussionmentioning
confidence: 99%